Optimal family policy in the presence of moral hazard, when the quantity and quality of children are stochastic - Alessandro Cigno; Annalisa Luporini (Institute for the Study of Labor (IZA), 2009)
We examine the second-best family policy under the assumption that both the number and the future earning capacities of the children born to a couple are random variables with probability distributions conditional on unobservable parental actions. Potential parents take their decisions without taking into account the effects of these actions on the government's future tax revenue. The second-best policy provides parents with credit and insurance, and allows them to appropriate the external benefits of their actions.
urn:nbn:de:101:1-20090608103
Keywords: D13; D78; D82; H31; J13; 330; Stochastic quantity and quality of children; moral hazard; population externalities; family allowances; scholarships; pensions; Familienpolitik; Second Best; Moral Hazard; Kinder; Bildungsinvestition; Familienleistungsausgleich; Studienfinanzierung; Theorie